REFORMULASI TATA KELOLA KEUANGAN MASJID MENUJU REVOLUSI MASJID 4.0 - Anita Putri; Raya Puspita Sari Hasibuan (Wahana Islamika: Jurnal Studi Keislaman, 2021)
The purpose of this study was to describe the application of technology to the financial management of mosques in Binjai City and, to conduct a SWOT analysis of mosque financial governance. This study uses field data, and analyzes the data using qualitative methods. The results of this study indicate that the implementation of technology in mosque financial management is very minimal, this is indicated by the large number of handwritten mosque financial reports because the administrators cannot operate computers. the administrators, the drawbacks are technological stuttering, minimal innovation, minimal training, lack of generation x, y, z, the opportunities they have are technological developments, modernist civilization, economic stability, and the threat is hedon culture and erosion of faith.